Implementation of Scouting Extracurricular Activities in Instilling Discipline and Responsibility: Implementasi Ekstrakurikuler Kepramukaan dalam Menanamkan Disiplin dan Tanggung Jawab - Syam, Nur; Khaerunnisa, Khaerunnisa; Nahira, Nahira; Nurdin, Syalsa Nabila; Ramadhani, Sri (Yayasan Ahmar Cendekia Indonesia, 2024)
Scouting is an educational process carried out outside the school and family environment, in the form of interesting, healthy, orderly, directed, and practical activities, and takes place in the open air with the basic principles of scouting. This study aims to instill an attitude of discipline and responsibility through the implementation of scouting extracurricular activities, especially in fostering discipline and responsibility in grade IV and V students at UPTD SDN 201 Inpres Tammu-Tammu. The method applied in this study is a descriptive qualitative method, which is used to describe the situation of scouting activities at UPTD SDN 201 INPRES TAMMU-TAMMU. The results of the study indicate that scouting activities, which include training in marching, smapore, ropes, and codes, can consistently form patterns of disciplined behavior among students through the application of strict rules and structured time management. Furthermore, student responsibility is formed through the implementation of individual and group tasks that are given in stages. However, this study also identified a number of obstacles, including the lack of supporting facilities and infrastructure and the lack of understanding among some students about the essence of scouting activities. Abstrak Kepramukaan merupakan proses pendidikan yang dilakukan di luar lingkungan sekolah dan keluarga, berupa aktivitas yang menarik, sehat, teratur, terarah, dan praktis, serta berlangsung di alam terbuka dengan prinsip dasar kepramukaan. Pengabdian ini bertujuan untuk menanamkan sikap disiplin dan tanggung jawab melalui pelaksanaan ekstrakurikuler kepramukaan, khususnya dalam menumbuhkan disiplin dan tanggung jawab pada siswa kelas IV dan V di UPTD SDN 201 Inpres Tammu-Tammu. Metode yang diterapkan dalam pengabdian ini adalah metode kualitatif deskriptif, yang digunakan untuk menggambarkan situasi kegiatan pramuka di UPTD SDN 201 Inpres Tammu-Tammu. Hasil dari pengabdian menunjukkan bahwa kegiatan kepramukaan, yang mencakup pelatihan baris berbaris, smapore, tali-temali, dan sandi-sandi, secara konsisten dapat membentuk pola perilaku disiplin di kalangan peserta didik melalui penerapan aturan yang ketat dan manajemen waktu yang terstruktur. Lebih lanjut, tanggung jawab peserta didik terbentuk melalui pelaksanaan tugas-tugas individu maupun kelompok yang diberikan secara bertahap. Meski demikian, pengabdian ini juga mengidentifikasi sejumlah kendala, antara lain minimnya sarana dan prasarana pendukung serta kurangnya pemahaman sebagian siswa tentang esensi dari kegiatan kepramukaan.